Immune-related adverse events caused by treatment with pembrolizumab in a patient with lung cancer who infected influenza virus. (2021) - Takemura, Masao; Motegi, Mitsuru; Kuroiwa, Yuya; Itai, Miki; Taguchi, Kohei; Umetsu, Kazue; Uchida, Megumi; Kouno, Shunichi; Sato, Mari; Masubuchi, Hiroaki; Yamaguchi, Aya; Yamaguchi, Koichi; et al.
Abstract: A 67-year-old man with stage IV B lung adenocarcinoma was treated with pembrolizumab. The patient was admitted to the hospital because of influenza on the day of the second cycle of pembrolizumab treatment. He was diagnosed with pneumonia and was treated with antiviral drugs and steroids. However, the patient eventually died. In this case, treatment with immune checkpoint inhibitors might have affected the immune response caused by influenza virus infection, that might have caused lung injury, which is an immune-related adverse event (irAE). Hence, it is important that, caution should be taken to prevent transmission of viral infection, and Therefore, it is important to prevent viral infections, but caution should also be paid to the possibility that infections may cause irAEs in patients with lung cancer.